Compartilhamento indevido de informações em redes sociais digitais: efetividade da legislação brasileira vigente no combate à violência contra a mulher - Vanderley, Shaennya Pereira (2021)
It is aimed to analyze the undue sharing of information on digital social networks that consist in cybercrime committed against women, based on the influence of social networks and privacy, the flow of information and digital law. We consider the legislative changes from Law No.12.737 of 2012, as known as the Carolina Dieckmann’s Law, which consider the technological device hack as a crime, are considered; 2018’s Law No.13.718, which considered offensive of sharing some private content, up to 5 years' imprisonment; 2018’s Law No.13.772 that changed the Penal Code and criminalizes unauthorized registration of intimate content; and the 2006’s Law No.11.340 (Maria da Penha Law), which considers the sharing of intimate content as psychological violence and violation of women's privacy. Methodologically, it adopts the inductive method and it is an exploratory and descriptive research, using the historical and comparative methods. The documentary method was used as a comparison with Brazilian legislation and with the Delegacia Especializada no Atendimento à Mulher (DEAM)’s Occurrence Reports from Sousa in Paraíba/Brazil, selected from January 2015 to January 2020 and recorded cases of forbidden information sharing. In addition to these records, interviews were made with the titular police chief and an agent from DEAM in the Sousa city. It uses a quantitative and qualitative approach and content analysis. The results identify and characterize the cases of improper information sharing, especially the irregular use of digital social networks in these crimes. In particular Facebook and WhatsApp as the social networks where crimes occur most frequently. Among the main factors that protects victims they are the qualification of professionals and the existence of a specialized network in help women. The intervening factors that stand out for the protection of the women’s rights victims of these crimes were social judgment, misinformation and the need for specific resources to investigate digital crimes. Betwixt the guidelines to support the victim and to arrested the criminal, there was the promotion of access to information, the availability of technological resources for investigation and the repression of unauthorized sharing in the virtual environment. It is concluded that the occurrence of crimes that use social networks aggravates the damage suffered by the victim and turns investigations harder. Despite the regulation and pertinence of Brazilian legislation and the existence of specialized professionals, there are social barriers that prevent the victims’ protection in these cases. It is emphasized that access to information improves the breaking down of social and cultural barriers, and it is necessary to promote it in order to make women aware of the existence and functioning of the specialized network and the possibility of protection, showing that there is protection for the victim.